On the influence of multiple cations on the in-gap states and phototransport properties of iodide-based halide perovskites. Issue 37 (17th September 2018) - Azulay, Doron; Levine, Igal; Gupta, Satyajit; Barak-Kulbak, Einav; Bera, Achintya; San, Granit; Simha, Shir; Cahen, David; Millo, Oded; Hodes, Gary; Balberg, Isaac
Abstract : In-gap states in solar cell absorbers that are recombination centers determine the cell's photovoltaic performance. Abstract : In-gap states in solar cell absorbers that are recombination centers determine the cell's photovoltaic performance. Using scanning tunneling spectroscopy (STS), temperature-dependent photoconductivity and steady-state photocarrier-grating measurements we probed, directly and indirectly, the energies of such states, both at the surface and in the bulk of two similar, but different halide perovskites, the single cation MAPbI3 (here MAPI) and the mixed cation halide perovskite, FA0.79 MA0.16 Cs0.05 Pb(I0.83 Br0.17 )3 (here MCHP). We found a correlation between the energy distribution of the in-gap states, as determined by STS measurements, and their manifestation in the photo-transport parameters of the MCHP absorbers. In particular, our results suggest that the in-gap recombination centers in the MCHP are shallower than those of MAPI. This can be one explanation for the better photovoltaic efficiency of the former.